Isolation and pathogenicity of a highly virulent group III porcine Getah virus in China - Wu, Yu; Gao, Xiaopeng; Kuang, Zhanpeng; Lin, Limiao; Zhang, Hao; Yin, Lijuan; Hong, Jiabing; Ren, Bohua (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionGetah virus (GETV) is a multi-host virus found in pigs, horses, and blue foxes. Clinically, GETV can cause fever, diarrhea, and reproductive disorders in pigs, representing significant threats to pig breeding. At present, few studies have examined the pathogenicity of GETV in pigs of different ages.MethodsIn the present study, a new strain, named GETV-QJ, was isolated from clinically ill pigs, and whole genome sequencing analysis was performed. Besides the pathogenicity of piglets and pregnant sows of this strain was further studied.Resultsthe results illustrated that the strain belonged to group III. The strain had 93.6%–96.3% homology with other subtypes, and its homology with the same subtype strain ranged 96.5%–99%. Further studies on the pathogenicity of the virus indicated that this strain caused severe diarrhea, fever, and intestinal and lung damage in 7-day-old piglets, resulting in their death. The piglet survival rate was 0%. In pregnant sows, this strain did not cause fever, death, or abortion, but it induced viremia, which affected the farrowing performance of sows and led to reduced piglet survival.DiscussionIn this study, we isolated a highly virulent group III and comprehensively established a pathogenic model of GETV in piglets and sows, providing a reference and guidance for the prevention and control of this infection.